Practising culture: The concept of a practice and the critique of reductionist conceptions of culture - Maicher, Sascha Georg Bernhart (University of Ottawa (Canada), 2008)
This thesis has two main aims. First, to argue that the concepts of culture used by a range of post-communitarian liberals in their political theory can be characterized as reductionist or essentialist, and to show the various difficulties such conceptions are prone to. Secondly, to try and outline a more useful conceptual tool for understanding the characteristic issues and conflicts of contemporary multiculturalism. Within contemporary liberalism one can distinguish an increasing willingness to contemplate the importance of cultural pluralism for political theory. I have chosen to examine three representative thinkers who have all attempted to integrate fundamental liberal principles with a newly developed sense of the significance of culture. As these attempts are in part a response to the communitarian critique of liberalism, I have designated these thinkers 'post-communitarian liberals. Chapters two, three, and four, explore the respective approaches of Charles Taylor, Will Kymlicka, and John Rawls. I argue that the conception of culture that each of these thinkers rely on is prone to the critiques of reductionist conceptions of culture, and this causes significant difficulties for their theories. After examining the post-communitarian liberals, chapter five explores the political philosophy of three exponents of the critique of reductionist conceptions of culture: Brian Barry, Joseph Carens, and Seyla Benhabib. While in each case there are problems with the approaches these thinkers take, I argue that Carens' emphasis on context, and Benhabib's appeal to deliberative democracy are aspects of those theories that are beneficial for political theories structured around non-reductionist approaches to culture. This thesis argues that political theory should focus on the concept of a 'practice' instead of culture. The concept of a practice is a revised version of that presented by Alasdair Maclntyre. While the concept of a practice has useful implications for political theorizing in diverse societies, the larger philosophical framework in which Maclntyre situates this concept is susceptible to many of the critiques of reductionist conceptions of culture. Thus it is necessary to show that the concept of a practice can be disentangled from the rest of Maclntyre's political theory. The conclusion of the thesis is that the best manner in which to address the characteristic conflicts and issues of diverse societies is a deliberative democracy whose debates are structured around the concept of a practice rather than that of a culture. This thesis argues that the concept of a 'practice' is more helpful for conceptualizing these debates and less prone to inaccurate generalizations regarding the citizens of modern societies.
Keywords: Philosophy.